2009
DOI: 10.1037/a0013984
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and behavioral evidence of syntactic priming in sentence comprehension.

Abstract: Event-related potentials and eye tracking were used to investigate the nature of priming effects in sentence comprehension. Participants read 2 sentences (a prime sentence and a target sentence), both of which had a difficult and ambiguous sentence structure. The prime and target sentences contained either the same verb or verbs that were very close in meaning. Priming effects were robust when the verb was repeated. In the event-related potential experiment, the amplitude of the P600 was reduced in target sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
174
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(204 citation statements)
references
References 67 publications
(121 reference statements)
28
174
2
Order By: Relevance
“…In the behavioral and ERP literature, findings of syntactic priming in comprehension seem to be almost completely dependent on repetition of the head-word (Arai et al, 2007;Branigan et al, 2005;Carminati et al, 2008;Ledoux et al, 2007;Tooley et al, 2009;Traxler & Tooley, 2007). On the other hand, syntactic priming in production is often observed without lexical repetition (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the behavioral and ERP literature, findings of syntactic priming in comprehension seem to be almost completely dependent on repetition of the head-word (Arai et al, 2007;Branigan et al, 2005;Carminati et al, 2008;Ledoux et al, 2007;Tooley et al, 2009;Traxler & Tooley, 2007). On the other hand, syntactic priming in production is often observed without lexical repetition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Syntactic priming in comprehension is shown in anticipatory eye-movements to pictures (Arai, van Gompel, & Scheepers, 2007;Carminati, van Gompel, Scheepers, & Arai, 2008;Thothathiri & Snedeker, 2008a;Traxler, 2008), in faster reading (Traxler & Tooley, 2008) and in picture-matching choices for ambiguous phrases (Branigan, Pickering, & McLean, 2005). In comprehension tasks, ERP studies revealed the attenuation of the P600 amplitude as a result of syntactic priming (Ledoux, Traxler, & Swaab, 2007;Tooley, Traxler, & Swaab, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sentence 5, the PP with the rifle is an instrument PP, because the noun in the PP represents the t object used (by an unnamed agent) to perform the action shot. 3 Previous experiments have shown that sentences with agent PPs prime reduced relative target sentences with agent PPs (Ledoux et al, 2007;Pickering & Traxler, 2004;Tooley et al, 2007;Traxler & Pickering, 2005;Traxler & Tooley, in press). The question that this experiment was designed to address was: Will agent and instrument sentences facilitate each other as much as they facilitate themselves?…”
Section: Methodsmentioning
confidence: 99%
“…Such effects are commonly observed in language production (e.g., Bock, 1986;Bock & Loebell, 1990;Branigan, Pickering, & Cleland, 2000) and, under the right circumstances, in online comprehension (Arai, van Gompel, & Scheepers, 2007;Ledoux, Traxler, & Swaab, 2007;Pickering & Traxler, 2004;Traxler & Pickering, 2005;Traxler & Tooley, in press). 1 For example, in an ERP study (Tooley, Traxler, & Swaab, 2007), reduced relative prime sentences, such as Sentences 1 and 2 below, appeared before a reduced relative target sentence, such as Sentence 3.…”
mentioning
confidence: 99%